2018 IEEE 29th Annual International Symposium on Personal, Indoor and Mobile Radio Communications (PIMRC) 2018
DOI: 10.1109/pimrc.2018.8580712
|View full text |Cite
|
Sign up to set email alerts
|

Localization Optimal Multi-user Beamforming with multi-carrier mmWave MIMO

Abstract: In this paper, we propose optimal beamforming strategies for a millimeter wave (mmWave) system consisting of multiple users based on the localization performance bounds. We consider a single base station (BS) with prior coarse knowledge of the users' positions and formulate the optimal beamforming problem in order to minimize the localization error consisting of Cramer Rao Lower Bounds (CRLBs) of delay, angle of departure (AoD) and angle of arrival (AoA) estimation at the mobile users. We first formulate the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Since we solved the optimization problems in equations (19) and (20) without the rank constraints to maintain convexity of the problem, we perform the rank-1 approximation of matrix F * n as for the single-user case in equation (17). We can see that objective function for min max fairness scheme in equation (19a) is a linear maximization problem with N 2 t N + 3 variables whereas that for the proportional fairness scheme is a non linear optimization problem in equation (20a) with N 2 t N + 3 U optimization variables.…”
Section: ) Proportional Fairness Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…Since we solved the optimization problems in equations (19) and (20) without the rank constraints to maintain convexity of the problem, we perform the rank-1 approximation of matrix F * n as for the single-user case in equation (17). We can see that objective function for min max fairness scheme in equation (19a) is a linear maximization problem with N 2 t N + 3 variables whereas that for the proportional fairness scheme is a non linear optimization problem in equation (20a) with N 2 t N + 3 U optimization variables.…”
Section: ) Proportional Fairness Strategymentioning
confidence: 99%
“…This SPEB is shown to be equivalent to a linear combination of the CRLB terms associated with delay and AoD estimates. Furthermore, [19] studies different fairness policies for localization error optimal beamforming in a multi-user multi-carrier system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that even a single BS can achieve promising positioning accuracy. Extensions to multiple-carrier and multiuser scenarios were studied in [7].…”
Section: Introductionmentioning
confidence: 99%
“…Practical positioning algorithms for the single-anchor mmWave MIMO system can be classified into two major categories, i.e., direct positioning [6] and two-stage positioning [4], [5], [7], [8]. The direct positioning aims at estimating the coordinates of the MS from the received signal directly, while the two-stage positioning first estimates the instantaneous channel realization: the channel gains, the angle of departure (AoD), the angle of arrival (AoA), and the time of arrival (ToA).…”
Section: Introductionmentioning
confidence: 99%